The Effect of Dual Role Conflict on the Performance of Female Employees with Work Life Balance as a Mediating Variable - La Rahu, Wa Rusni; Marwan, Marwan; Nurlaila, Nurlaila (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to determine the effect of multiple role conflict on the performance of female employees mediated by work life balance. This research is a quantitative research with data collection techniques using a questionnaire. The sample in this study were female employees, totaling 56 employees. This research used non-probability sampling technique with purposive sampling method. The analytical tool used is path analysis with the help of the SPSS 29 program. The results showed that multiple role conflict has a positive and significant effect on employee performance, multiple role conflict has a negative and significant effect on work life balance, work life balance has a positive effect and significant effect on employee performance, and work life balance can be a mediating variable between multiple role conflicts on employee performance.